About the diversity of Dasypodidae (Xenarthra, Cingulata) along the Late Miocene of northwestern Argentina: The case of the Salicas Formation. (December 2022) - Barasoain, Daniel; González Ruiz, Laureano R.; Brandoni, Diego
Abstract: The deposits of the Neogene Salicas Formation crop out along the north area and western flanks of the Velasco range, in the northern area of La Rioja Province, Argentina. Previous known remains from the formation include Notoungulata, Litopterna, and Rodentia, in addition to several Xenarthra, including Pilosa (sloths) and Cingulata Glyptodontidae and Dasypodidae. In this contribution, new remains recovered from the Salicas Formation at the area of El Degolladito are described and referred to distinct species of Dasypodidae: Vetelia ghandii Esteban and Nasif 1996, Chasicotatus peiranoi Esteban and Nasif 1996, Chorobates villosissimus (Reig, 1958), Macrochorobates scalabrinii (Moreno and Mercerat, 1891), Paleuphractus argentinus (Moreno and Mercerat, 1891), and Prozaedyus sp. This association of dasypodids increases their diversity for this formation and suggests a Late Miocene age for the bearing levels. Additionally, this association shows great affinities with those reported for other Late Miocene localities along northwestern Argentina, including several species that represent endemic taxa not shared with the Pampean Region. In this context, the differences of Dasypodidae taxa between these regions may be related to both orogenic and paleoambiental features. Highlights: New Dasypodidae (Xenarthra, Cingulata) are recorded for the Salicas Formation. The Dasypodidae association supports a Late Miocene age for the bearing levels of the Salicas Formation. The recorded taxa show great affinities with those reported for other late Miocene localities along northwestern Argentina. Northwestern Argentina includes several endemic species of Dasypodidae, not shared with the Pampean Region.